2020
DOI: 10.1155/2020/5460168
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude, and Practices on Water, Sanitation, and Hygiene among Rural Residents in Tigray Region, Northern Ethiopia

Abstract: Background. Poor hygienic practices, inadequate water supply, and poor sanitary conditions play a major role in the spread of infectious diseases. Lack of knowledge, attitude, and practices (KAP) on WASH is one of the most imperative causes for transmission of infectious diseases. Therefore, the aim of this study was to assess knowledge, attitude, and practice of rural residents on water, sanitation, and hygiene in Tigray, Ethiopia. Methods. A community-based cross-sectional study was conducted from June to Ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 14 publications
3
21
2
1
Order By: Relevance
“…Further, when women are socially independent, they could participate in social organizations and share knowledge about the benefit of improved sanitation service so that struggle to establish the service. In the same way, a study from rural part of Ethiopia showed that having good information about the benefits of WASH services was associated with having these services at home (49,50). Though it had variation in the types of indicators used to measure empowerment, this finding broadly supports the work of other studies in this area linking sanitation with women's empowerment (48,51).…”
Section: Discussionsupporting
confidence: 62%
“…Further, when women are socially independent, they could participate in social organizations and share knowledge about the benefit of improved sanitation service so that struggle to establish the service. In the same way, a study from rural part of Ethiopia showed that having good information about the benefits of WASH services was associated with having these services at home (49,50). Though it had variation in the types of indicators used to measure empowerment, this finding broadly supports the work of other studies in this area linking sanitation with women's empowerment (48,51).…”
Section: Discussionsupporting
confidence: 62%
“…This result was high compared to other studies that the overall mean knowledge of adults in terms of water safety, sanitation and hygiene was 78.1% [6]. And in another study good knowledge and practice on WASH were observed in 42.2% and 49.2% of the respondents, respectively [14]. This high level of knowledge and practice in the city could be mainly due to the continuous input of the Ministry of Health and the Eritrean Government in improving the life standards of the community in general and the proper utilization and usage of latrines and sanitation through the Community Lead Total Sanitation (CLTS) programs of increasing awareness and triggering processes.…”
Section: Discussionmentioning
confidence: 55%
“…Despite these results and even though almost all self-reported that regular hand washing is very important, but during practical observation the narrative changes. Mothers' hands were not clean in 20.8% of them and only 23.5% of the households had soap at the toilet during the investigators visit, which is better than similar Ethiopian study (14.98%) [14]. This shows that the practice of hand washing with soap after defecation is questionable.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Globally one-third of women experience intimate partner violence (IPV) [6]. These violations are a serious public health concern throughout the world, but it's notably present in low and middle-income countries (LMICs) particularly in Sub-Saharan Africa including Ethiopia, where 38.83% of the women abused by their intimate partner [7,8,9,10,11,12,13]. Women's reproductive right needs due attention because of its violence happens worldwide and it is a serious challenge for the health of women [1,7,14].…”
Section: Introductionmentioning
confidence: 99%